Biotechnology and development challenges and opportunities for Asia - International Conference on Biotechnology and Development: Challenges and Opportunities for Asian Region New Delhi, India) (2002; Chaturvedi, Sachin; Rao, S. R.; Research and Information System for the Non-aligned and Other Developing Countries (Singapore Institute of Southeast Asian Studies, 2004)
Contributed articles presented earlier at the International Conference on Biotechnology and Development: Challenges and Opportunities for Asian Region, February 26-27, 2002 at New Delhi, India organized by RIS.
"Research in Information System for the Non-Aligned and Developing Countries, New Delhi."
Keywords: Biotechnology -- Asia -- Congresses; Biotechnology industries -- Asia -- Congresses